Potential combinations of Platelet Rich Plasma (PRP) and chitosan in burn wound management: a review - Gede Wara Samsarga; I Gusti Putu Hendra Sanjaya; Agus Roy Rusly Hariantana Hamid; Komang Januartha Putra Pinatih; Ni Made Ratih Purnama Dewi (Intisari Sains Medis, 2020)
Background:Â  The development of new modality for burn wound healing is necessary to reduce morbidity and mortality of burn injury. PRP (Platelet Rich Plasma) is one of potential modality for burn injury because of its ability to deliver various growth factors to initiate and accelerate tissue healing and regeneration. Clinical efficacy of PRP is frequently disturbed because inconsistency and inefficiency of growth factor release in PRP. To increase the effectiveness of PRP in wound healing and increase the bioavailability of growth factor, PRP can be combined with a carrier that can control continuous release of growth factors. Chitosan is one of biomaterial that potential to use because of its biodegradability characteristic and biological activity that important for burn wound healing and prevent the formation of scar tissue in a burn injury. Researches have shown that chitosan is an effective carrier to facilitate growth factor release continuously to burn wound.Aims: This review aims to review potential Combinations of PRP (Platelet Rich Plasma) & Chitosan in Burn WoundConclusion:Â With chitosan ability to facilitate burn wound healing and as an effective carrier, combination of PRP and chitosan is a promising modality for burn wound healing.